Teacher Math Anxiety Relates to Adolescent Students' Math Achievement. (February 2018) - Ramirez, Gerardo; Hooper, Sophia Yang; Kersting, Nicole B.; Ferguson, Ronald; Yeager, David
Elementary school teachers' math anxiety has been found to play a role in their students' math achievement. The current study addresses the role of teacher math anxiety on ninth-grade students' math achievement and the mediating factors underlying this relationship. Using data from the National Mindset Study, we find that higher teacher math anxiety is associated with lower math achievement. This relationship is partially mediated by the students' perception that their teacher believes not everyone can be good at math and is not explainable by teachers' usable knowledge to teach mathematics. In subsequent analyses, we find that higher teacher math anxiety relates to a reduction in process-oriented (as opposed to ability-oriented) teaching practices, which in turn predict students' perception of teacher mindset. We argue that math anxious teachers and their use of particular teaching strategies have the potential to shape students' math achievement and their perceptions of what their teacher believes about math.